2011
DOI: 10.1371/journal.pone.0022775
|View full text |Cite
|
Sign up to set email alerts
|

Increased Diacylglycerols Characterize Hepatic Lipid Changes in Progression of Human Nonalcoholic Fatty Liver Disease; Comparison to a Murine Model

Abstract: Background and AimsThe spectrum of nonalcoholic fatty liver disease (NAFLD) includes steatosis, nonalcoholic steatohepatitis (NASH), and progression to cirrhosis. While differences in liver lipids between disease states have been reported, precise composition of phospholipids and diacylglycerols (DAG) at a lipid species level has not been previously described. The goal of this study was to characterize changes in lipid species through progression of human NAFLD using advanced lipidomic technology and compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 33 publications
18
90
0
Order By: Relevance
“…1B ). Such a pattern is in accordance with a previous study fi nding differences between the livers of normal, steatotic, and cirrhotic patients in PUFAcontaining GPLs ( 47 ). Most of the sphingolipid species that differed in both the liver and plasma across histological 6-phosphogluconate ( P = 0.048) shown in supplementary Fig.…”
Section: Identifi Cation Of Potential Biomarkerssupporting
confidence: 92%
“…1B ). Such a pattern is in accordance with a previous study fi nding differences between the livers of normal, steatotic, and cirrhotic patients in PUFAcontaining GPLs ( 47 ). Most of the sphingolipid species that differed in both the liver and plasma across histological 6-phosphogluconate ( P = 0.048) shown in supplementary Fig.…”
Section: Identifi Cation Of Potential Biomarkerssupporting
confidence: 92%
“…The enzymes PS synthases PTDSS1 and PTDSS2 that catalyse the production of PS by condensation of phosphatidylcholine and phosphatidylethanolamine, respectively, were significantly downregulated in NASH patients. The significant changes in the level of PS in cirrhotic (severe stage of NASH) livers was previously reported in a study on changes in lipid species in subjects with cirrhotic livers compared with healthy controls 47 . Given that PS is essential for hepatocytes, we hypothesize that decreased activity of these enzymes may be associated with a decrease in the endogenous level of serine, which is the second most connected node in our identified Reporter Subnetworks (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms4083supporting
confidence: 60%
“…Taken together, the results suggest that the changes in the level of PS in the liver 47 as well as the relative increase in the homocysteine blood level 49 is caused by decreased level of endogenous serine. To test this hypothesis, we checked the expression level of enzymes that catalyse the biosynthesis of serine in the liver of NASH patients, and it was observed that the expression levels of PHGDH, PSAT1, PSPH in serine synthesis pathway (SSP), and SHMT1 and SHMT2 enzymes were significantly downregulated (Supplementary Table 6).…”
Section: Reporter Metabolites Subsystems In Hmr Databasementioning
confidence: 66%
“…An almost 4-fold increase relative to total lipid content was measured upon short-time fasting, an 0.5-fold increase upon KO-effect, whereas super stress returned the fasting DG level to levels measured in ATGL-KO mice. We conclude that substantial enhancement of DG amounts in the liver ( 6,26 ), particularly in hepatocyte LDs ( 11 ), can be considered a further indicator of insulin resistance; this does not apply to the smaller DG increases caused by ATGL defi ciency, however. In line with this, a long-term study with liver-specifi c ATGL-KO mice revealed progressive hepatosteatosis, but unchanged insulin tolerance; a compensatory mechanism was suggested by reduced DG acyltransferase 2 mRNA (responsible for TG synthesis) and increased lipolysomal activity for TG degradation ( 17 ).…”
Section: Discussionmentioning
confidence: 74%